Phenomenological research of meaning-making for the bereavement of a close person - Stanaitytė, J.; Kočiūnas, R. (Psichologija, 2013)
The study analyzes the phenomenon of meaning making for the bereavement of a person with whom they had close relationships, based on the experience of seven research participants. All of them had been nursing a relative till the death from an incurable disease. The study aims to identify the essential structure and get a clear and systematic description of meaning-making for the bereavement. All the data were collected in depth semi-structured interviews (lasting 50–80 minutes). The main question of the interview was “please remember and describe the specific situation or the moment when you understood that you have lost your a close person. What does this understanding mean to you?” An analysis of the interviews was performed on the basis of the A. Giorgi phenomenological psychological analysis method. At the end of the study, there were discovered and identified 13 essential aspects, 5 directions, and 2 fundamental spaces of meaning-making for the bereavement. All the findings were shared by every participant. The results were summarized into a single definition. First of all, results of the research have revealed that meaning-making for the bereavement is a process rather than a one-off event or situation. The results show that the meaning-making for the bereavement of a close person is mainly expressed by qualitative changes in relationships and in the world-view. In the area of qualitative changes in the relationships, it is worth to distinguish changes in the relationship with the relative one: here one can find a big concern for nursing the loved one, experiencing the ongoing existence of a dead relative and feeling a strong spiritual support from them because of the deep relations before death. The other changes in the area are qualitative changes in social relations.The area of qualitative changes in the world-view unfolds in three levels. The first level concerns the evaluation of experiences in time perspective: change in the attitude towards bereavement is reavealed; the evaluation of its emotional states becomes objective; and all these aspects are summarized as a valuable lesson for personal grow. The second level concerns the identification and appreciation of discovered benefits: the relevance of living here and now; the importance of changes in the personal system of the relevance of living here and now; the importance of changes in the personal system of values; and the recognition that relative’s attitude towards death affected the worldview of others. The third level unfolds the discovery of fundamental truths: the meaning of the experience of loss is perceived as metaphysical and beyond the limits of the human mind; the temporality of existence and the unknowability of death is recognized.
Keywords: bereavement; sense-making; phenomenological research